Phase Space Analysis of the Zero-Order Bessel Beam and Superimposed Zero-Order Bessel Beams - Cruz, Franulfo L.Dela (Archīum Ateneo, 2023)
The authors analyzed some phase-space properties of zero-order Bessel beams through direct computation of their Wigner function. As indicated in the conclusion, modelling Bessel beams of higher order may be more useful for experimental purposes, or to check the validity of the result. Modelling the superimposed zero-order Bessel beam is significant in some applications.